Perbankan Syariah di Indonesia: Manajemen dan Strategi Pemasaran - Ahmad Khoiri; Chuzaimah Batubara (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Islamic banks in Indonesia have progressed very rapidly compared to other banks, Islamic banks in Indonesia have issued several products including financing products, these products include the principle of buying and selling with an installment system or Sharia KPR, financing for construction and working capital for SMEs, principles of SME working capital, lease-purchase principles, loan principles, and order principles. Islamic banks are banks that operate without relying on interest. Islamic banks, also known as interest-free banks, Islamic banks are financial or banking institutions whose operations and products are developed based on Al-Qur'an and and Hadith of the Prophet Muhammad SAW. The marketing strategy of Islamic banks is a step that must be taken in marketing banking products or services that aim to increase sales. The increase in sales was oriented towards funding products, customer orientation, service quality improvement and fee-based income.